2013
DOI: 10.1177/1029864913493800
|View full text |Cite
|
Sign up to set email alerts
|

Is there a peak in popular music preference at a certain song-specific age? A replication of Holbrook & Schindler’s 1989 study

Abstract: This is a replication and further interpretation of Holbrook and Schindler's study "Some Exploratory Findings on the Development of Musical Tastes" from 1989. Holbrook and Schindler's investigation has been widely acknowledged in music psychology as well as in consumer research and has helped further the assumption that people generally cling to music and other cultural objects they get to know in late adolescence/early adulthood. In the current replication study, a peak in musical preference across songspecif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 6 publications
8
39
1
1
Order By: Relevance
“…Recent evidence in music psychology research has revealed that musical preferences continue to evolve during adulthood (Bonneville-Roussy et al, 2013), thereby contradicting previous findings in the area (e.g. Hemming, 2013;Holbrook & Schindler, 1989). Age trends in musical preferences have been subject to much debate, and very few studies have systematically investigated these differences.…”
Section: Age Differences In Musical Preferencesmentioning
confidence: 83%
“…Recent evidence in music psychology research has revealed that musical preferences continue to evolve during adulthood (Bonneville-Roussy et al, 2013), thereby contradicting previous findings in the area (e.g. Hemming, 2013;Holbrook & Schindler, 1989). Age trends in musical preferences have been subject to much debate, and very few studies have systematically investigated these differences.…”
Section: Age Differences In Musical Preferencesmentioning
confidence: 83%
“…They invited 108 participants to rate 28 popular songs released between 1932 and 1986 and demonstrated an inverted U-shaped curve, such that preference ratings peaked for songs that had been released at the age of 24 years. Numerous studies have found this same pattern of a greater liking of songs released during the SP (e.g., Hemming, 2013 ; Janssen et al, 2007 ; Krumhansl, 2017 ). Other researchers have focussed more specifically on the ability to recognise music from different eras and the extent to which music activates the retrieval of autobiographical memories (e.g., Cady et al, 2008 ; Schulkind et al, 1999 ).…”
mentioning
confidence: 57%
“…En síntesis, la música considerada significativa durante la adolescencia pareciera ser la más importante de nuestras vidas (North y Hargreaves, 2002). Más allá de la etapa adolescente y juvenil, los oyentes adultos continúan mostrando una preferencia general por los artistas o músicos que fueron populares durante su adolescencia tardía o adultez temprana (Haack 1988;Hemming 2013;Holbrook y Schindler 1989;North y Hargreaves 1995). Este hecho, de algún modo confirma la importancia de acrecentar las opciones de escucha en esta etapa de la vida y específicamente en enseñanza media.…”
Section: Repercusión De Las Preferencias Musicales En La Definición Dunclassified